2019
DOI: 10.1111/bph.14711
|View full text |Cite|
|
Sign up to set email alerts
|

Histidine‐rich glycoprotein ameliorates endothelial barrier dysfunction through regulation of NF‐κB and MAPK signal pathway

Abstract: Background and Purpose Microvascular barrier breakdown is a hallmark of sepsis that is associated with sepsis‐induced multiorgan failure. Histidine‐rich glycoprotein (HRG) is a 75‐kDa plasma protein that was demonstrated to improve the survival of septic mice through regulation of cell shape, spontaneous ROS production in neutrophils, and adhesion of neutrophils to vascular endothelial cells. We investigated HRG's role in the LPS/TNF‐α‐induced barrier dysfunction of endothelial cells in vitro and in vivo and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 56 publications
(65 reference statements)
2
27
0
Order By: Relevance
“…The cellular cytoskeleton and glycocalyx regulate the morphology of the metabolically active endothelial cells [ [23] , [24] , [25] ]. The endothelium disruption may be due to the cytoskeletal reorganization and pathogen recognition by cellular receptors [ [26] , [27] , [28] , [29] ]. Lung endothelial hyperpermeability is the cause and consequence of inflammatory lung disease, including ALI or ARDS [ 30 , 31 ].…”
Section: Human Pulmonary Vasculaturementioning
confidence: 99%
“…The cellular cytoskeleton and glycocalyx regulate the morphology of the metabolically active endothelial cells [ [23] , [24] , [25] ]. The endothelium disruption may be due to the cytoskeletal reorganization and pathogen recognition by cellular receptors [ [26] , [27] , [28] , [29] ]. Lung endothelial hyperpermeability is the cause and consequence of inflammatory lung disease, including ALI or ARDS [ 30 , 31 ].…”
Section: Human Pulmonary Vasculaturementioning
confidence: 99%
“…Notably, the effective concentrations of HRG on human vascular endothelial cells were within the same range (Gao et al, 2019). HRG inhibited the PMA-induced upregulation of the expression of the activation epitope on CD11b on NLCs as observed in neutrophils (Wake et al, 2016).…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, it repeatedly yielded a considerable number of NLCs. In previous studies (Gao et al, 2019;Wake et al, 2016), HRG was observed to induce the round shape of neutrophils, their smooth surface, and few microvilli. These neutrophils could easily pass through the microchannels and cause the lowest levels of spontaneous ROS production and less adhesion to the vascular endothelial cells and the artificial polystyrene wear.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…When endothelial cells are damaged, there is an increase in capillary permeability and plasma exudation, which results in swelling of the joint (Middleton et al, 2004). Breakdown of the endothelial barrier function can also promote the adhesion of neutrophils to vascular endothelial cells, resulting in abnormal coagulation function, microvascular leakage, tissue hypoperfusion, and ultimately multiple organ failure (Opal and van der Poll, 2015;Gao et al, 2019). The permeability of endothelial cells increases with lipopolysaccharide and interferon-γ stimulation.…”
Section: Protection Of the Endothelial Barrier Functionmentioning
confidence: 99%